ChemInform Abstract: Facile Synthesis of Novel N4‐Substituted 2‐(Trifluoromethyl)‐tetrahydrobenzothieno[ 2, 3‐d]pyrimidine Derivatives. Issue 19 (May 2015) - Wang, Fasong; Gao, Hui; Yang, Ping; Wang, Yan; Song, Xinjian
Abstract: The title compounds are obtained by a facile three‐step synthesis starting from easily accessible starting materials under mild reaction conditions.